2006
DOI: 10.3748/wjg.v12.i18.2958
|View full text |Cite
|
Sign up to set email alerts
|

Gastric signet-ring adenocarcinoma presenting with breast metastasis

Abstract: Breast metastases from gastric cancer are extremely rare. A case report of a 37-year-old female with breast inflammatory invasion and ascites is described. Breast biopsy revealed carcinomatous invasion of the lymphatics from adenocarcinoma cells with signet-ring features. Estrogen (ER) and progesterone receptors (PR) and c-erb-B2 were negative. Upper gastrointestinal endoscopy revealed a prepyloric ulcerative mass. Histopathologic examination of the lesion showed infiltration from a high-grade adenocarcinoma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
42
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 19 publications
1
42
0
4
Order By: Relevance
“…The immunoprofile of breast metastases from stomach adenocarcinomas is positive for adenocarcinoma markers such as CK7, CK20, and carcinoembryonic antigen (CEA) while negative for ER, PR, GCDFP-15, as well as for C-erB-2 (in up to 20% it can be positive) (Boutis et al, 2006;Parrell Soler et al, 2011). It has been demonstrated that immunohistochemical staining for CK alone cannot distinguish primary breast cancer and metastatic breast carcinoma from gastric cancer (Sato et al, 2008).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The immunoprofile of breast metastases from stomach adenocarcinomas is positive for adenocarcinoma markers such as CK7, CK20, and carcinoembryonic antigen (CEA) while negative for ER, PR, GCDFP-15, as well as for C-erB-2 (in up to 20% it can be positive) (Boutis et al, 2006;Parrell Soler et al, 2011). It has been demonstrated that immunohistochemical staining for CK alone cannot distinguish primary breast cancer and metastatic breast carcinoma from gastric cancer (Sato et al, 2008).…”
mentioning
confidence: 99%
“…The presence of a heterogeneous echoic mass in the left adnexal area may suggest metastatic ovarian involvement while more persuasive proof was lacking. Although the metastatic involvements of breast and ovary are extremely rare and there are only five cases that have been reported, the selective invasion of hormone-dependent organs may explain why breast and ovary are involved (Boutis et al, 2006).…”
mentioning
confidence: 99%
See 3 more Smart Citations